Pengembangan Alat Permainan Edukatif (APE) Robot Jati Diri sebagai Media Pembelajaran untuk Implementasi Kurikulum Merdeka PAUD - Lina Eka Retnaningsih; Mahfuzah Saniah; Aidillah Suja; Sri Amanda; Karni; Enggel Purnama Wulandari (Universitas Islam Lamongan, 2025)
The Merdeka Curriculum for Early Childhood Education introduces a novel component termed the Self-Identity element; however, learning media that adequately support its associated learning outcomes remain limited. This study aimed to develop an educational play tool, the